Respuesta :
we use elimination method.
x+y = -2
2x-y = 5
_______
3x = 3
3x/3 = 3/3
x = 1
As we found the x-value, we now have to find out y-value by substituting the x-value into any equation from the given.
x+y = -2
1+y = -2
-1 -1
y = -3
So, the answer is (1,-3).
x+y = -2
2x-y = 5
_______
3x = 3
3x/3 = 3/3
x = 1
As we found the x-value, we now have to find out y-value by substituting the x-value into any equation from the given.
x+y = -2
1+y = -2
-1 -1
y = -3
So, the answer is (1,-3).
one way is ellimination metahto where we add
add them together
x+y=-2
2x-y=5 +
3x+0y=3
3x=3
divide by 3
x=1
subsitute
x+y=-2
1+y=-2
subtract 1
y=-3
answer
x=1
y=-3
answer is in form (x,y) and is (1,-3)
add them together
x+y=-2
2x-y=5 +
3x+0y=3
3x=3
divide by 3
x=1
subsitute
x+y=-2
1+y=-2
subtract 1
y=-3
answer
x=1
y=-3
answer is in form (x,y) and is (1,-3)